Properties of a Solution of an Inhomogeneous Hyperbolic Equation with Random Right-Hand Side - Dovhai, B. V. (Ukrains’kyi Matematychnyi Zhurnal, 2005)
We consider an inhomogeneous hyperbolic equation with zero initial and boundary conditions and a random centered sample-continuous Gaussian right-hand side. We establish conditions for the existence of a solution of the first boundary-value problem of mathematical physics in the form of a series uniformly convergent in probability in terms of a covariance function. An estimate for the distribution of the supremum of a solution of this problem is obtained.